Florida's Geological History - Ginger M. Allen; Martin B. Main (EDIS)
Florida's geological history has been principally affected by changing sea levels, which influenced the formation of bedrock, the resulting soils, and surface topography. These geological factors influence Florida's plant communities, which support animal communities. Geological history, therefore, has influenced Florida's  environment and ecology in the past, during the present, and will continue to have effects in the future. This document is Fact Sheet WEC 189, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: May 2005.